PROMOTING ACTIVE COMMUNICATION USING GAME-BASED ICT AND AI-POWERED TOOLS - ATAMURATOVA, Mehribon Kamarbekovna (The Lingua Spectrum, 2025)
One of the continuing problems in EFL (English as a Foreign Language) classrooms is active verbal interaction that seriously challenges almost every learner. AI-powered tools and game-based ICT can create interactive environments where students can practice speaking without feeling nervous and uncomfortable. Through a thorough and systematical review of studies published between 2020 and 2025, this research has been investigated to better understand how game-based ICT and AI-powered tools can encourage active communication among EFL learners. This study conducted an extensive literature review focusing on game-based ICT and AI tools in EFL contexts from the Scopus, Web of Science and ERIC databases, using inclusion criteria. According to extensive research, students can greatly improve their speaking abilities and considerably boost their confidence in communication and readiness to talk in a foreign language by using AI chatbots with LLM technology, voice-based conversational agents, and gamified ICT systems. These advanced technologies' key benefits include very detailed step-by-step instructions, immense stress relief, and immediate personalized feedback. Employing the combination of game-based ICT and AI-powered tools in EFL contexts has shown valuable promise for enhancing significantly students’ communication abilities in a foreign language learning environment. Future research especially needs to give a particular focus on developing well-designed studies that follow ethical standards and create teaching methods which work at different educational levels.